Faktor-faktor Langsung dan Tak Langsung yang Memengaruhi Entrepreneurial Intention - Andika Isma (Bata Ilyas Journal of Accounting, 2022)
Â This study aims to determine the direct and indirect effect of entrepreneurial self-efficacy, subjective norm, locus of control, entrepreneurial attitude on entrepreneurial intention. This study uses a descriptive explanatory quantitative approach that describes the relationship between variables and a population of 492 students. The sampling technique used is proportional random sampling with a total of 220 students from the Faculty of Economics, Makassar State University. The results showed that directly and indirectly entrepreneurial self-efficacy, subjective norm, locus of control, entrepreneurial attitude had a significant effect on entrepreneurial intention. Based on the results of the research that has been done, this research can be a source of information or reference for teaching staff or lecturers so that they can direct and guide students regarding the development of entrepreneurship skills, students are expected to further deepen their skills related to business management.Penelitian ini bertujuan untuk mengetahui pengaruh langsung dan pengaruh tidak langsung dari entrepreneurial self-efficacy, subjective norm, locus of control, entrepreneurial attitude terhadap entrepreneurial intention. Penelitian ini menggunakan pendekatan kuantitatif jenis Descriptive Explanatory yang menggambarkan hubungan antar variabel dengan populasi sebesar 492 Mahasiswa. Teknik pengambilan sampel menggunakan Proportional Random Sampling berjumlah 220 mahasiswa Fakultas Ekonomi Universitas Negeri Makassar. Hasil penelitian menunjukkan bahwa secara langsung dan tidak langsung entrepreneurial self-efficacy, subjective norm, locus of control, entrepreneurial attitude berpengaruh signifikan terhadap entrepreneurial intention. Berdasarkan hasil penelitian yang telah dilakukan, penelitian ini dapat menjadi sumber informasi atau referensi untuk para tenaga pengajar atau dosen agar bisa mengarahkan dan membimbing mahasiswa terkait pengembangan keterampilan berwirausaha, mahasiswa diharapkan lebih memperdalam keterampilan terkait pengelolaan bisnis.Keywords:Entrepreneurial Self-Efficacy, Entrepreneurial Intention, Entrepreneurial Attitude; Locus Of Control; Subjective Norm